Evolutionary perspectives on seed consumption and dispersal by fishes - Correa, Sandra Bibiana; Winemiller, Kirk O.; Lopez-Fernandez, Hernan; Galetti, Mauro (Amer Inst Biological Sci, 2007)
Fishes probably were the first vertebrate seed dispersers, yet little research has examined this phenomenon. We review evidence of fruit and seed consumption by fishes, and analyze the evolution of frugivory and granivory using South American serrasalmids as a model. Frugivory and granivory are observed among diverse fish taxa worldwide, although most reports are from the Neotropics. Frugivory and granivory among serrasalmids apparently are derived from omnivory, with powerful jaws and specialized dentition appearing as major adaptations. No particular fruit traits seem to be associated with seed dispersal by fishes (ichthyochory). Recent experimental evidence of ichthyochory suggests that fishes can influence riparian vegetation dynamics. Because of deleterious human impacts on aquatic ecosystems worldwide, many critical interactions between plants and fishes have been disrupted before they could be studied. Exotic frugivorous fishes have recently become established on foreign continents, with unknown ecological consequences.
Keywords: ichthyochory; evolutionary ecology; flooded forests; seed predation; Serrasalmidae